2011
DOI: 10.1007/s10658-011-9791-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and detection of Pythium and Phytophthora species associated with grapevines in South Africa

Abstract: Replant and decline diseases of grapevines not only cause quantitative and qualitative yield losses, but also result in extra costs when vineyards have to be replanted. This study investigated the role of Pythium and Phytophthora in the decline syndrome in South Africa by determining (1) the species associated with nursery and established vines, and (2) pathogenicity of Ph. sp. niederhauserii and P. vexans relative to known grapevine pathogens. Quantitative real-time PCR (qPCR) assays were also developed for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 39 publications
(48 reference statements)
1
29
0
Order By: Relevance
“…The symptoms in spring were failure to leaf out, death of the scion and sprouting from the rootstock. The name Phytophthora niederhauserii is a nomen nudum due to the publication of the species in previous manuscripts using this name before the official description of the species, according to Kroon et al (2012) (Martini et al 2007, Luongo et al 2010, Spies et al 2011. To remedy this situation, we herein validate the name of this species as Phytophthora niederhauserii Z.G.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…The symptoms in spring were failure to leaf out, death of the scion and sprouting from the rootstock. The name Phytophthora niederhauserii is a nomen nudum due to the publication of the species in previous manuscripts using this name before the official description of the species, according to Kroon et al (2012) (Martini et al 2007, Luongo et al 2010, Spies et al 2011. To remedy this situation, we herein validate the name of this species as Phytophthora niederhauserii Z.G.…”
mentioning
confidence: 74%
“…In South Africa the new species was isolated from grapevine nurseries and established vineyards and was shown to cause stunting of grapevines in greenhouse pathogenicity trials (Spies et al 2011). The isolation of P. niederhauserii from the crowns of nursery vines in that study indicated the potential of the species to cause crown rot in grapevines (Spies et al 2011) . P. niederhauserii also was found in 2009 on almonds in Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…Pythium vexans isolates, which were identified using ITS sequence data, were obtained from (i) roots and soils of grapevines collected in nurseries and established vineyards (Spies 2010), (ii) citrus orchard soils , and (iii) apple orchard soil and roots (Tewoldemedhin et al 2010). No more than two isolates from a single grapevine or orchard (apple and citrus) were included for characterisation, resulting in a P. vexans collection of 35 isolates from grapevine, eight from apple and three from citrus (Table 1).…”
Section: Isolatesmentioning
confidence: 99%
“…In South Africa, P. vexans isolates (identified using ITS sequence data) have recently been recovered from, and shown to be pathogenic to both grapevines (Spies 2010) and apple seedlings (Tewoldemedhin et al 2010). Additionally, this species has also been recovered from citrus orchards .…”
Section: Introductionmentioning
confidence: 99%
“…By monitoring either directly amplified PCR products bound with a fluorescent dye or complementary probe, or indirectly generated fluorescence applying the exonuclease activity of Taq polymerase, proportions of the PCR products or fluorescence could be determined directly (Okubara et al, 2005 Kernaghan et al (2008) also fully amplified ITS regions of P. ultimum and P. irregulare group I and IV in American ginseng field soil samples by using specifically designed primers. Additionally, qPCR was implemented to identify and quantify P. vexans based on the small subunit (SSU) and ITS region of the genome (Bent et al, 2009;Spies et al, 2011b). There are more than 20 different primer sets working specifically on a broad range of Pythium spp.…”
Section: Pythium Quantificationmentioning
confidence: 99%